Cloud mask over snow‐/ice‐covered areas for the GCOM‐C1/SGLI cryosphere mission: Validations over Greenland. Issue 21 (13th November 2014) - Chen, Nan; Li, Wei; Tanikawa, Tomonori; Hori, Masashiro; Aoki, Teruo; Stamnes, Knut
Abstract: Cloud detection is a critically important first step required to derive many satellite data products. A novel cloud detection algorithm designed for the cryosphere mission of Global Climate Observation Mission First Climate satellite/Second Generation Global Imager (GCOM‐C1/SGLI) is presented. This reflectance‐based cloud detection scheme mainly utilizes only two short wavelength infrared channels with dynamic thresholds that depend on Sun‐satellite viewing geometry to perform accurate cloud detection over snow/ice surfaces in high latitude as well as high‐elevation regions. Profiles of atmospheric absorbing and scattering molecules as well as surface elevation are considered in the determination of the thresholds for the resulting snow/ice cloud mask (SCM) algorithm. Image‐based tests and statistical results have been used to validate the performance of the SCM over the Greenland plateau. Statistics using collocated Cloud‐Aerosol Lidar with Orthogonal Polarization and Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua observations over Greenland in 2007 show that over snow/ice surfaces the performance of the SCM is generally better than that of the MODIS cloud mask. Key Points: Cloud mask over snow‐ and ice‐covered surface Thresholds are dynamically determined from the solar‐viewing geometry Surface elevation and atmospheric profiles are also considered